Pengaruh Varian Produk Dan Harga Terhadap Keputusan Pembelian Pada Toko Centra Batik Di Bandar Lampung - Epi Parela (Jurnal Manajemen dan Bisnis (JMB), 2020)
AbstractInfluence of Product and Price Variances on Purchasing Decision at Centra Batik shop in Bandar Lampung. The purpose of this study is to determine whether the variant of products and prices simultaneously or partially influence the purchase decision. This research uses quantitative method. The number of samples in this study is 75 respondents. Multiple Linear Regression Test, F Test, T Test, and Adjusted R2 Test. The results of this study showed that the results of Multiple Linear Regression Y = 0.064 + 0.571X1 + 0.424X2. The F test results indicate the Variant Product variable, and the Price together have a significant influence on the Purchase decision. T test results show that the product and price variants partially affect the purchase decision. The result of the determination coefficient (adjusted R2) obtained by 0.624 (62.4%) shows the product variant and the price can explain the purchase decision. Keywords: Product Variant, Price, Purchase Decision